ANALYZING ENGLISH TEACHER CANDIDATES’ TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE IN PEDAGOGICAL FORMATION EDUCATION - İrfan TOSUNCUOĞLU (International Journal of Eurasia Social Sciences, 2018)
This research has been conducted in order to analyze the technological pedagogical content knowledge of senior level students of the Department of English Language and Literature of Karabük University, who have undertaken pedagogical education. The study has been carried out on 82 students in the spring term of 2017-2018 AY. In this study a general survey model has been utilized. Furthermore, the scale developed by Horzum, Akgün and Öztürk (2014) has been implemented as a tool of data collection. In the analysis of data based on sub-problems, percentage, frequency, arithmetic mean, standard deviation and T-test methods have been applied. In the testing of significance of differences, .05 has been settled on as the threshold of significance. The results of the research has shown that the technological content knowledge of English teaching candidates who have taken Pedagogical formation education is augmented. However, the pedagogical pedagogical content knowledge of teaching candidates differed significantly depending on the gender variable. But in considering the variables of technological access and technology utilization level, no statistically significant difference was found.